KEPUASAN PENGGUNA SISTEM INFORMASI AKUNTANSI PADA LEMBAGA PERKREDITAN DESA DI KABUPATEN BULELENG - Swandewi, Luh Putri; Ariyanto, Dodik; Dewi, Luh Gede Krisna (E-Jurnal Akuntansi; Vol 19 No 3 (2017), 2017)
The success of an accounting information system in managing village finances is very important to note. Good-bad performance of an information system can be seen through user satisfaction. User satisfaction will improve the productivity, efficiency and effectiveness of reporting organization in using information systems. The purpose of this research is to assess the success of using Accounting Information System (SIA) by using DeLone & McLean Model (1992). The population of this research is all of LPD in Buleleng Regency. The sample used purposive sampling, with sampling criterion that is LPD which has amount of asset rank 30 biggest in Buleleng Regency. The questionnaires are returned and are worth to be processed as many as 90 questionnaires. Data analysis technique used is multiple linear regression. The results showed that the top management support positively affect the satisfaction of SIA users in LPD Buleleng Regency, the quality of the system has a positive effect on the satisfaction of SIA users in LPD Buleleng District, and the quality of information positively affect the satisfaction of SIA users in LPD Buleleng District.
Keywords: Peak Management Support, System Quality, Information Quality, User Satisfaction